Perioperative management of coronavirus patient and critical care concerns - Nidhi Kaeley; Prakash Mahala; Rohan Bhatia; Suman Choudhary (Wolters Kluwer Medknow Publications, 2021)
Coronavirus disease 2019 caused by SARS-COV-2 virus was first detected in China in December 2019. The World Health Organization declared it as a public health emergency of international concern on January 30, 2020. It is a beta coronavirus with identical genome as that of bat coronavirus hinting to bats as a natural host. It causes a wide spectrum of clinical symptoms. They include fever, dry cough, fatigue, loss of smell, diarrhea, and severe pneumonia leading to acute respiratory distress syndrome. The elderly population and those with underlying comorbidities are more prone to severe pneumonia and higher mortality. At present, India is in the stage 2 of local transmission of SARS-COV-2 infection. However, Indian government in collaboration with the Indian Council of Medical Research is taking stringent steps to prevent stage 3 transmission that is community spread. In this review article, we discuss evidence-based principles and guidelines of infection control and perioperative management of patients in COVID-19 times. The emphasis is on the use of personal protective equipment's and hand hygiene steps to prevent viral transmission by and to the anesthetist and other frontline health-care workers as well as patients.